The correlations between the average semester growth rates of syntactic and lexical complexity in L2 writing development at secondary school - Rokoszewska, Katarzyna (Neofilolog, 2024)
The article is devoted to the development of language complexity in a relatively under-researched area of adolescent writing from the point of view of Complex Dynamic Systems Theory (CDST). It describes the second part of a panel study which aimed to examine the relationships among the average semester growth rates (ASGRs) of specific measures of syntactic and lexical complexity within and between these two subsystems in writing in English as a foreign language at the secondary school level. The study involved the analysis of The Written English Developmental Corpus of Polish Learners (WEDCPL). The corpus, which comprises over 1900 essays, was created on the basis of 21 repeated measurements conducted in a group of 100 secondary school learners during a period of three years. With respect to the specific measures of syntactic and lexical complexity, the study indicated that nominalization developed faster than subordination and coordination, and that lexical variation developed faster than lexical density and sophistication per semester. Moreover, the relationships between the ASGRs of both syntactic and lexical measures were more supportive within than between the subsystems. The main pedagogical implication for English language teachers refers to fostering more coordinated development of language complexity at secondary school in the EFL context.